An Examination of Global Mindset and International Market Opportunities among SMEs. Issue 2 (22nd February 2018) - Lazaris, Miria; Freeman, Susan
Abstract: In this study, we refine theories of global mindset and strategy complexity by using a multiple case study approach to comparatively examine global mindset and internationalization among different types of small and medium-sized enterprises (SMEs), including INVs, late international SMEs and domestic SMEs. We focus on a relatively low-technology knowledge-intensive sector, food and beverages, as a direct comparison. The findings demonstrate two distinct dimensions of global mindset, cultural (cosmopolitanism), and strategic (cognitive complexity), which contribute directly toward SME internationalization and should be considered in future research. This study extends our knowledge of the inextricable influence of global mindset on the internationalization of SMEs and illustrates how managerial cognitions can enable them to overcome resource and knowledge constraints required to enter and compete in international markets. We refine theory, offer theoretical propositions, and develop a conceptual framework, underpinned by the dynamic capabilities perspective, and show that among low-technology knowledge-intensive SMEs, cosmopolitanism and cognitive complexity have different effects on internationalization, and that cosmopolitanism is more salient for explaining early and rapid internationalization.